Maternal Obesity in Pregnancy Developmentally Programs Adipose Tissue Inflammation in Young, Lean Male Mice Offspring - Alfaradhi, Maria Z. (Endocrinology, 2016)
Obesity during pregnancy has a long-term effect on the health of the offspring including risk of developing the metabolic syndrome. Using a mouse model of maternal diet-induced obesity, we employed a genome-wide approach to investigate the microRNA (miRNA) and miRNA transcription profile in adipose tissue to understand mechanisms through which this occurs. Male offspring of diet-induced obese mothers, fed a control diet from weaning, showed no differences in body weight or adiposity at 8 weeks of age. However, offspring from the obese dams had up-regulated cytokine (Tnfα; P < .05) and chemokine (Ccl2 and Ccl7; P < .05) signaling in their adipose tissue. This was accompanied by reduced expression of miR-706, which we showed can directly regulate translation of the inflammatory proteins IL-33 (41% up-regulated; P < .05) and calcium/calmodulin-dependent protein kinase 1D (30% up-regulated; P < .01). We conclude that exposure to obesity during development primes an inflammatory environment in adipose tissue that is independent of offspring adiposity. Programming of adipose tissue miRNAs that regulate expression of inflammatory signaling molecules may be a contributing mechanism.